Scenario Decomposition for 0-1 Stochastic Programs: Improvements and Asynchronous Implementation - Ryan, Kevin; Rajan, Deepak; Ahmed, Shabbir (2016 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW), 2016)
A recently proposed scenario decomposition algorithm for stochastic 0-1 programs finds an optimal solution by evaluating and removing individual solutions that are discovered by solving scenario subproblems. In this work, we develop an asynchronous, distributed implementation of the algorithm which has computational advantages over existing synchronous implementations of the algorithm. Improvements to both the synchronous and asynchronous algorithm are proposed. We test the results on well known stochastic 0-1 programs from the SIPLIB test library and is able to solve one previously unsolved instance from the test set.